Differentiation-related epigenomic changes define clinically distinct keratinocyte cancer subclasses - Solé-Boldo, Llorenç; Raddatz, Günter; Gutekunst, Julian; Gilliam, Oliver; Bormann, Felix; Liberio, Michelle S; Hasche, Daniel; Antonopoulos, Wiebke; Mallm, Jan-Philipp; Lonsdorf, Anke Susanne; Rodríguez Paredes, Manuel; Lyko, Frank (Molecular systems biology, 2022)
Keratinocyte cancers (KC) are the most prevalent malignancies in?fair-skinned populations, posing a significant medical and economic burden to health systems. KC originate in the epidermis and mainly comprise basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC). Here, we combined single-cell multi-omics, transcriptomics, and methylomics to investigate the epigenomic dynamics during epidermal differentiation. We identified ~3,800 differentially accessible regions between undifferentiated and differentiated keratinocytes, corresponding to regulatory regions associated with key transcription factors. DNA methylation at these regions defined AK/cSCC subtypes with epidermal stem cell- or keratinocyte-like features. Using cell-type deconvolution tools and integration of bulk and single-cell methylomes, we demonstrate that these subclasses are consistent with distinct cells-of-origin. Further characterization of the phenotypic traits of the subclasses and the study of additional unstratified KC entities uncovered distinct clinical features for the subclasses, linking invasive and metastatic KC cases with undifferentiated cells-of-origin. Our study provides a thorough characterization of the epigenomic dynamics underlying human keratinocyte differentiation and uncovers novel links between KC cells-of-origin and their prognosis.